Effect of Gold Nanoparticle Size on Regulated Catalytic Activity of Temperature-Responsive Polymer−Gold Nanoparticle Hybrid Microgels - Palida Pongsanon; Akifumi Kawamura; Hideya Kawasaki; Takashi Miyata (Gels, 2024)
Gold nanoparticles (AuNPs) possess attractive electronic, optical, and catalytic properties, enabling many potential applications. Poly(N-isopropyl acrylamide) (PNIPAAm) is a temperature-responsive polymer that changes its hydrophilicity upon a slight temperature change, and combining PNIPAAm with AuNPs allows us to modulate the properties of AuNPs by temperature. In a previous study, we proposed a simpler method for designing PNIPAAm–AuNP hybrid microgels, which used an AuNP monomer with polymerizable groups. The size of AuNPs is the most important factor influencing their catalytic performance, and numerous studies have emphasized the importance of controlling the size of AuNPs by adjusting their stabilizer concentration. This paper focuses on the effect of AuNP size on the catalytic activity of PNIPAAm–AuNP hybrid microgels prepared via the copolymerization of N-isopropyl acrylamide and AuNP monomers with different AuNP sizes. To quantitatively evaluate the catalytic activity of the hybrid microgels, we monitored the reduction of 4-nitrophenol to 4-aminophenol using the hybrid microgels with various AuNP sizes. While the hybrid microgels with an AuNP size of 13.0 nm exhibited the highest reaction rate and the apparent reaction rate constant (kapp) of 24.2 × 10−3 s−1, those of 35.9 nm exhibited a small kapp of 1.3 × 10−3 s−1. Thus, the catalytic activity of the PNIPAAm–AuNP hybrid microgel was strongly influenced by the AuNP size. The hybrid microgels with various AuNP sizes enabled the reversibly temperature-responsive on–off regulation of the reduction reaction.